Analisis Aspek Pemasaran, Aspek SDM dan Aspek Lingkungan Industri Material Bangunan CV. Istana Batako Kecamatan Kandangan - Decy Selvina; Hayati, Hayati; Siti Norkhaliza; Sabrina Kaisya Putri; Muhammad Firliadi Noor Salim (MANABIS: Jurnal Manajemen dan Bisnis, 2024)
This study aims to explore the feasibility of CV. Istana Batako by conducting an in-depth analysis of marketing, human resources (HR), production processes, and environmental aspects. CV. Istana Batako, specializing in building materials such as paving and bricks, has been operating since 2012 in Kandangan. In terms of marketing, this research identifies locally focused promotional strategies, strategic product distribution, and a customer base dominated by government and residential sectors. For HR, the company empowers approximately 40 local employees through a piece-rate payroll system, fostering social ties with the surrounding community. The production process combines modern machinery and manual techniques to produce high-quality products adhering to K250 standards, supported by laboratory testing. From an environmental perspective, the company demonstrates a commitment to sustainability through the use of local raw materials and responsible waste management. The findings reveal that the synergy between personal marketing, effective HR management, efficient production, and environmental awareness is key to the company’s success and competitiveness. This study recommends expanding digital marketing strategies, modernizing production tools, and enhancing environmental management systems to achieve better business sustainability.